Análise de transmissão congênita de Toxoplasma gondii (Nicole & Manceaux, 1909) em ovinos em duas propriedades no município de Rosário do Sul, RS, Brasil - Silva, Karin Lucianne Monti de Vasconcellos (2001)
This study investigates the possibility of Toxoplasma gondii congenital transmission in lambs. Results are describes of antibodies IgG and IgM classes detection anti-Toxoplasma gondii in sequential serum samples from lambs and their mothers , without apparently symptoms. IgG antibodies were quantified by indirect imunofluorescence (IFI) and indirect hemaglutination (HAI). The antibodies IgM were detected using HAI method after sera treatement with 2- mercaptoethanol, using comercial kits. Titers higher than 16 for hemaglutination and 20 for imunofluorescence were considered positive. From the beginning two hundred and forty-seven sera samples were analysed and, within three months interval, more one hundred twenty sera samples were taken only from lambs. There were one hundred seventy five sheeps from 1999 production (one ewe had twins) and seventy two sheeps from 2000 production, in two farms, both situated in the rural area of Rosário do Sul county, RS, Brazil. Through serological analysis were detected twenty two lambs (18,33%) whose showed titers in the first test, which declined and also negativated the imunological response in the second test, denoting antibodies passive transference. Only at four lambs (3,33%), whose mothers presented early infection and, titers growed from first to second test, suggested posssible congenital transmission of Toxoplasma gondii.